2012
DOI: 10.1038/modpathol.2012.110
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of skeletal development: a cluster analysis of 206 bone tumors reveals diagnostically useful markers

Abstract: The molecules Indian hedgehog (IHH), SP7 (also known as osterix), sex-determining region Y-box 9 (SOX9), runt-related transcription factor 2 (RUNX2) and TWIST1 regulate the normal differentiation of osteo-and chondrogenic cells from precursors during skeletal development and remodeling. The aberrant function of the same molecules has been implicated in the pathogenesis of bone tumors. Preliminary studies suggest that antibodies against these molecules have practical, diagnostic or prognostic utility in tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 44 publications
(57 reference statements)
4
29
0
Order By: Relevance
“…In order to assess whether denosumab treatment induces differentiation of the neoplastic cells of GCTB along the osteoblastic lineage, we examined the expression of RUNX2 and SATB2 in pretreatment and post-treatment tumour specimens. In agreement with previous studies,15 16 we observed that GCTB stains for both markers, although the staining for SATB2 tended to be less diffuse and presented in small groups of neoplastic cells, often associated with osteoid matrix production, whereas RUNX2 was expressed in most neoplastic cells. While RUNX2 expression remained unchanged after treatment, SATB2 was detected only in a subset of cells in areas of mature bone formation, and was not detected in cellular areas or in association with collagen matrix production.…”
Section: Discussionsupporting
confidence: 93%
“…In order to assess whether denosumab treatment induces differentiation of the neoplastic cells of GCTB along the osteoblastic lineage, we examined the expression of RUNX2 and SATB2 in pretreatment and post-treatment tumour specimens. In agreement with previous studies,15 16 we observed that GCTB stains for both markers, although the staining for SATB2 tended to be less diffuse and presented in small groups of neoplastic cells, often associated with osteoid matrix production, whereas RUNX2 was expressed in most neoplastic cells. While RUNX2 expression remained unchanged after treatment, SATB2 was detected only in a subset of cells in areas of mature bone formation, and was not detected in cellular areas or in association with collagen matrix production.…”
Section: Discussionsupporting
confidence: 93%
“…Mutation of SATB2 , in both mouse models and cases of human germline deletion, leads to a similar phenotype of craniofacial malformations and osteoblastic dysregulation . SATB2 knock‐out mice have skeletal anomalies, supporting the idea that SATB2 plays a vital role in skeletal development and osteoblastic differentiation, probably through interaction with runt‐related transcription factor‐2 (RUNX2, also known as CBFA1) …”
Section: Introductionmentioning
confidence: 75%
“…SATB2 IHC was performed on 26 cases stained as whole slides and on 22 cases on previously constructed tissue microarrays (TMAs). The construction of the TMAs has been previously reported …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Although it has been suggested that SP7 could be a useful marker for assisting in the differential diagnosis of bone tumors, the number of immunohistochemical studies on the expression of this marker in these neoplasms is limited. 20,21 At present, there is insufficient information available to determine whether SP7 has any practical use as an osteoblastic differentiation marker in the diagnosis of bone and soft-tissue tumors.…”
Section: Satb2 As An Osteoblastic Markermentioning
confidence: 99%